Outer membrane vesicles engineered to express membrane-bound antigen program dendritic cells for cross-presentation to CD8+ T cells. (June 2019) - Schetters, Sjoerd T.T.; Jong, Wouter S.P.; Horrevorts, Sophie K.; Kruijssen, Laura J.W.; Engels, Steef; Stolk, Dorian; Daleke-Schermerhorn, Maria H.; Garcia-Vallejo, Juan; Houben, Diane; Unger, Wendy W.J.; den Haan, Joke M.M.; Luirink, Joen; et al.
Graphical abstract: Abstract: Outer membrane vesicles (OMVs) are vesicular nano-particles produced by Gram-negative bacteria that are recently being explored as vaccine vector. The fact that OMVs can be efficiently produced by a hypervesiculating Salmonella typhimurium strain, are packed with naturally-occurring adjuvants like lipopolysaccharides (LPS), and can be engineered to express any antigen of choice, makes them ideal candidates for vaccinology. However, it is unclear whether OMVs induce dendritic cell (DC)-mediated antigen-specific T cell responses and how immune activation is coordinated. Here, we show that OMVs induce maturation of human monocyte-derived DCs, murine bone marrow-derived DCs and CD11c+ splenic DCs. OMV-induced DC maturation was dependent on the presence of LPS and the myeloid differentiation primary response 88 (MyD88) adapter protein downstream of toll-like receptor signaling. Importantly, OMVs did not induce pyroptosis/cell death, but instead provided a significant survival benefit in DCs over non-stimulated DCs. OMVs displaying a sizeable ovalbumin fragment at the vesicle surface induce potent cross-presentation in BMDCs and splenic CD11c + DCs to OTI CD8 + T cells, dependent on MyD88. Interestingly, the OMV-induced preference to cross-presentation was only partly dependent on the BATF3-dependent CD8a + professional cross-presenting DC subset. Hence, an OMV-specific programming of DCs that induces maturation and provides a survival benefit for antigen presentation to T cells is identified. Additionally, for the first time, antigen-specific and potent cross-presentation of antigen-loaded OMVs to CD8 + T cells is demonstrated. These data provide mechanistical insight into the processes needed for the DC-mediated cross-presentation of OMV-derived antigens to CD8 + T cells with implications for therapeutic strategies. Statement of Significance: Bacteria are primarily known to cause disease. However, recent research has focused on using engineered bacteria and its byproducts as vaccine agents. In particular, outer membrane vesicles (OMVs) have shown promise in eliciting potent immunity against a variety of pathogens. While most vaccines rely on the generation of antibodies, the control of viral replication and tumor growth is driven by cytotoxic CD8 + T cells induced by dendritic cells (DCs). As such, there is a dire need for vaccines that use DCs to elicit CD8 + T cell responses. Studying OMVs as engineered biomaterial and its interaction with DCs allows tailored induction of immunity. This study includes important findings on OMV-dendritic cell interactions and for the first time supports OMVs as vehicles for the induction of antigen-specific CD8 + T cell responses. Additionally, important mechanistical insight into the molecular pathways needed for the cross-presentation of OMV-derived antigens to CD8 + T cells is provided.